(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Context: UTI is one of the most common infection in nephrotic syndrome and may be a cause of delayed steroid response. Objective:To observe the impact of urinary tract infection on steroid response in idiopathic nephrotic syndrome children aged 2-6 years. Study design: Quasi experimental study Study period & place: Pediatric ward of Chittagong Medical College Hospital, Chittagong from 01.01.2009 to 31.12.2009. Participants: 52 Nephrotic syndrome children aged 2-6 years with typical clinical features Group A: Nephrotic syndrome with UTI, Group B: Nephrotic syndrome without UTI. Methods: Heat coagulation test, urine for R/M/E and C/S was done in every patient. Steroid was given according to standard regimen. Date of starting of steroid was recorded. Antibiotic was given in group A cases according to C/S report. Patients were followed for clinical and urinary remission. Group A and B were compared for remission time achieved by statistical method. Results: A male preponderance was noted about 57.7% against female about 42.3%. Generalized swelling of body & scanty micturation found in cent percent study group. Ascitis was found in 23.08%. Scrotal/labial swelling 7.69%.UTI developed in 30.8% of patients of NS. Male female ratio is 1:1. Infection delayed the remission of proteinuria. Mean remission time of NS without UTI patients was 7.39 days and with UTI patients was 9.31 days. In statistical analysis, mean remission time in group A =9.31+2.24 days(mean + SD), in group B=7.39+2.51 days(mean + SD), P value = <0.05, statistically significant. Conclusion: UTI in nephrotic syndrome causes delayed remission of proteinuria and may be asymptomatic.It should be screened in every nephrotic syndrome children routinely. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21046